Catalyst composite, catalyst precursor composite and producing method of catalyst composite

The catalyst composite on a ceramic honeycomb base material addresses catalyst replacement and low-temperature activity issues, facilitating easy exchange and high methanation activity for efficient methane production.

JP2025007488APending Publication Date: 2025-01-17PROTERIAL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023108920
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing methanation catalysts face challenges with catalyst replacement difficulty due to large sizes and low carbon dioxide conversion rates, especially at low temperatures, and the methanation reaction's exothermic nature complicates efficient methane production.

Method used

A catalyst composite is developed with a ceramic honeycomb base material supporting a methanation reaction catalyst, featuring a water absorption of 170 g/L or less, allowing easy catalyst exchange and high activity at low temperatures through a method involving hydrosol immersion, drying, and heat treatment to support a catalytically active metal.

Benefits of technology

The catalyst composite enables easy catalyst replacement and maintains high methanation activity at low temperatures, ensuring sufficient catalyst support and efficient methane production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007488000001_ABST
    Figure 2025007488000001_ABST
Patent Text Reader

Abstract

To provide a catalyst composite easy in catalyst exchange and high in activity of methanation at low temperature, a catalyst precursor composite, and a producing method thereof.SOLUTION: A catalyst composite in which a methanation reaction catalyst for methanation by reacting a gas containing at least one of carbon dioxide or carbon monoxide with hydrogen is supported on a ceramic honeycomb substrate, wherein the catalyst is composed of a catalyst active metal and a carrier supporting the same, the carrier is characterized in that a water absorption per unit volume of the carrier supported on the ceramic honeycomb substrate is 170 g / L or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite in which a catalyst for the methanation reaction of carbon dioxide (CO2) or carbon monoxide (CO) is supported on a ceramic honeycomb substrate, a composite in which a precursor of a catalyst for the methanation reaction is supported on a ceramic honeycomb substrate, and methods for producing the same. [Background technology]

[0002] In recent years, global warming has become a serious problem worldwide. There is an urgent need to reduce emissions of carbon dioxide (CO2), which is the greenhouse gas that causes global warming and has the greatest impact. As a solution, methanation technology, which synthesizes methane (CH4), the main component of natural gas, from hydrogen (H2) and carbon dioxide (CO2), has been attracting attention.

[0003] The methanation reaction shown in formula 1 is called the Sabatier reaction, and known catalysts include Ni-based catalysts and Ru-based catalysts supported on alumina, ceria, or zirconia. Catalysts are used in a variety of shapes, but cylindrical, ring-shaped, spherical, and other shapes are commonly used. On the other hand, there are also known examples of using composites in the form of a catalyst coated with catalyst powder on a ceramic honeycomb-structured substrate.

[0004] CO2+ 4H2→ CH4+ 2H2O…(Formula 1)

[0005] Here, Patent Document 1 discloses a CO2 methanation catalyst that converts carbon dioxide into methane using hydrogen, the catalyst comprising a carrier and a catalytic component, the carrier comprising one or more elements selected from the group consisting of Ce, La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and the catalytic component comprising Ni supported on the carrier. It is disclosed that the catalyst can be in the form of pellets, plates, powder, honeycomb, etc.

[0006] Non-Patent Document 1 describes the results of evaluating the methanation performance of a catalyst in which GDC (gadolinium-doped-ceria) is used as a support and 50 wt% Ni is supported as a catalytically active metal, which is applied to a monolith substrate made of cordierite. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-155227 A [Non-patent literature]

[0008] [Non-Patent Document 1] A.Vita et al., Applied Catalysis B:Environmental 226(2018)384-395 Summary of the Invention [Problem to be solved by the invention]

[0009] However, when the methanation catalyst as in Patent Document 1 is used in the form of pellets or powder, a large amount of catalyst of several mm in size is packed in the reactor, so that it is not easy to replace the catalyst when it deteriorates. Also, according to Non-Patent Document 1, when a honeycomb-shaped catalyst is used, the CO2 conversion rate (the ratio of introduced carbon dioxide that is converted) is low at 300°C or less. The methanation reaction of carbon dioxide using hydrogen is an exothermic reaction, and the higher the reaction temperature, the more difficult it is to produce methane, so a methanation catalyst that has high activity at low temperatures is desired.

[0010] In order to solve the above-mentioned problems, an object of the present invention is to provide a catalyst composite, a catalyst precursor composite, and methods for producing the same, which are easy to replace and have high methanation activity at low temperatures. [Means for solving the problem]

[0011] The first aspect of the present invention is a catalyst composite in which a catalyst for a methanation reaction for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide with hydrogen is supported on a ceramic honeycomb substrate, the catalyst comprising a catalytically active metal and a carrier supporting the metal, and the carrier supported on the ceramic honeycomb substrate has a water absorption per unit volume of 170 g / L or less.

[0012] In addition, a second aspect of the present invention is a catalyst precursor composite in which a precursor of a methanation reaction catalyst for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide with hydrogen is supported on a ceramic honeycomb substrate, the precursor comprising a precursor of a catalytically active metal or a compound produced from the precursor, and a carrier supporting the precursor or the compound, the carrier being supported on the ceramic honeycomb substrate and having a water absorption per unit volume of 170 g / L or less.

[0013] In addition, a third aspect of the present invention is a method for producing a catalyst composite in which a methanation reaction catalyst for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide with the ceramic honeycomb substrate is supported on the ceramic honeycomb substrate, and the method includes a carrier-supported material preparation step of immersing the ceramic honeycomb substrate in a hydrosol containing a carrier material, followed by drying and heat treatment to produce a carrier-supported material in which the carrier is supported on the ceramic honeycomb substrate; a catalyst precursor composite preparation step of impregnating the carrier support with an aqueous solution of a salt of a catalytically active metal, followed by drying and heat treatment to produce a catalyst precursor composite in which a precursor of the catalytically active metal is supported; and a catalyst reduction step of heat-treating the catalyst precursor composite to reduce the precursor of the catalytically active metal to produce the catalytically active metal. Effect of the Invention

[0014] According to the present invention, it is possible to provide a catalyst composite which is easy to replace and has high methanation activity at low temperatures. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 illustrates one embodiment of a catalytic composite of the present invention. [Diagram 2] FIG. 1 is a flow diagram illustrating a method for producing a catalytic composite of the present invention. [Diagram 3] 1 is a graph showing the relationship between the water absorption amount of the carrier-supported material (before supporting a catalyst precursor) and the methane conversion rate in the catalyst composites of Examples 1 to 6 and Comparative Examples 7 to 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Catalyst Composites and Catalyst Precursor Composites> The catalyst composite of the present invention is a catalyst for a methanation reaction for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide with hydrogen, the catalyst being characterized in that the catalyst comprises a catalytically active metal and a carrier for supporting the metal, and the carrier supported on the ceramic honeycomb substrate has a water absorption per unit volume of 170 g / L or less.

[0017] In addition, the catalyst precursor composite of the present invention is characterized in that a catalyst precursor for a methanation reaction for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide with hydrogen is supported on a ceramic honeycomb substrate, the catalyst precursor comprises a precursor of a catalytically active metal or a compound produced from the precursor of the catalytically active metal, and a carrier supporting the precursor and the compound, and the water absorption per unit volume of the carrier supported on the ceramic honeycomb substrate is 170 g / L or less.

[0018] Hereinafter, an embodiment of the present invention will be described with reference to Figures 1 and 2. First, a catalyst composite and a catalyst precursor composite will be described, and then a manufacturing method for obtaining the composite will be described. However, the present invention is not limited to the embodiment described here, and appropriate combinations and improvements can be made without departing from the technical concept of the invention.

[0019] An embodiment of the catalyst composite will be described. In this specification, a numerical range expressed using "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits. The upper and lower limits can be arbitrarily combined.

[0020] An example of the configuration of a catalyst composite is shown in Figure 1. The catalyst composite 100 is configured by supporting a catalyst for methanation reaction (hereinafter simply referred to as catalyst) 120 on a ceramic honeycomb substrate 110.

[0021] The ceramic honeycomb substrate 110 has an outer peripheral wall 111, partition walls 112 disposed inside the outer peripheral wall 111, and a plurality of cells 113 defined by the partition walls 112. The plurality of cells 113 adjacent to each other across the partition walls 112 pass through the ceramic honeycomb substrate in parallel from one end face to the other end face, and can pass a raw material gas that is a mixture of a gas containing carbon dioxide or carbon monoxide and hydrogen. A catalyst 120 is supported on the surface of the partition walls 112, and a methanation reaction occurs when the raw material gas comes into contact with the catalyst 120. The partition walls 112 are porous, and pores 114 communicate with the partition walls 112.

[0022] The illustrated ceramic honeycomb substrate 110 has a cylindrical shape, but is not limited to this shape and may be, for example, a substantially polygonal column shape. The size of the ceramic honeycomb substrate 110 is also not particularly limited and can be appropriately determined according to the size of a reaction tube in which the catalyst composite 100 is placed. For example, it is preferable that the outer diameter Do of the end face is 10 to 100 mm, and the length H from one end face to the other end face is 20 to 200 mm.

[0023] Although the cross-sectional shape of the illustrated cells 113 perpendicular to the penetration direction is quadrangular, the shape is not limited and may be, for example, substantially polygonal or substantially circular. The density of the cells 113 in the ceramic honeycomb substrate 110 is not particularly limited, but is preferably 180 to 1200 cpsi (cells per square inch).

[0024] There is no particular limitation on the material of the ceramic honeycomb substrate 110. Since the partition walls 112 are porous, for example, a sintered body such as cordierite, silicon carbide, or a composite of these can be suitably used. The material of the outer peripheral wall 111 is also not particularly limited, and may be the same material as the partition walls 112 or a different material.

[0025] The catalyst 120 is composed of a catalytically active metal 121 and a carrier 122 for supporting the catalytically active metal 121 on the partition wall 112. The catalyst 120 is desirably composed of the catalytically active metal 121 having high activity for methanation of carbon dioxide or carbon monoxide and the carrier 122, and the catalytically active metal 121 preferably contains at least one of Ni, Fe, Co, Cu, and Ru. The carrier 122 is supported in the form of a film on the partition wall 112, and the film formed by the carrier 122 has pores for supporting the catalytically active metal 121. Such a carrier 122 preferably contains at least one of alumina (Al2O3), ceria (CeO2), and zirconia (ZrO2).

[0026] To ensure sufficient catalytic activity, the mass of the catalytically active metal 121 should be less than the volume of the catalytic composite 100 (=π·(Do / 2) 2 It is preferable that the mass of the carrier 122 is 12 g / L or more relative to the volume of the catalyst composite 100 in order to sufficiently reduce the amount of water absorption in the catalyst composite 100, and it is preferable that the mass of the carrier 122 is 40 g / L or more relative to the volume of the catalyst composite 100 in order to shorten the carrier supporting step described later as much as possible. It is more preferable that the mass is 50 g / L or more and 250 g / L or less.

[0027] Moreover, the water absorption amount when the ceramic honeycomb substrate 110 supports the carrier 122 is 170 g / L or less. The water absorption amount is the amount of water that the ceramic honeycomb substrate 110, the ceramic honeycomb substrate supporting the carrier (support-supported material), the catalyst precursor composite, and the catalyst composite 100 can contain, and is expressed as the mass of water absorbed per unit volume (g / L). The water absorption amount can be measured by making the ceramic honeycomb substrate 110 or the ceramic honeycomb substrate 110 supporting the carrier absorb water, and calculating using the mass of the absorbed water and the volume of the ceramic honeycomb substrate 110. A specific method will be described later in the examples. The volume that the ceramic honeycomb substrate 110 can absorb water is roughly equivalent to the volume of the pores 114. When the catalyst 120, catalyst precursor, and carrier 122 are supported, the volume of the pores of the carrier 122 may be included, but when the particle diameter of the carrier 122 is on the nano-order, the volume of the pores formed by the carrier particles is small, and the substantial amount of water absorption is due to the volume of the pores of the ceramic honeycomb substrate 110. In the carrier support, the carrier 122 is supported on the surface of the partition wall 112 and the surface of the pore 114, and the amount of water that the pore 114 can absorb is reduced compared to before the carrier is supported. That is, the smaller the amount of water absorption, the more the amount of the carrier 122 is supported, and the more the carrier 122 is present on the surface of the partition wall 112 of the ceramic honeycomb substrate 110, so that it is possible to support the catalytically active metal 121 on the carrier 122 and to ensure a sufficient amount of catalyst for the methanation reaction. Conversely, when the water absorption amount is large, it indicates that the amount of the carrier 122 supported is small, and it is assumed that a sufficient amount of catalyst cannot be secured for the methanation reaction due to the occurrence of portions on the surface of the partition walls 112 of the ceramic honeycomb substrate 110 where the carrier 122 is not supported, or due to the state where only a very small amount of the carrier 122 is supported. In some cases, the catalytically active metal 121 may be supported too densely on the carrier 122, or the catalytically active metal 121 may not necessarily be supported on the carrier 122. The water absorption amount when the carrier 122 is supported on the ceramic honeycomb substrate 110 is more preferably 160 g / L or less.

[0028] In addition, the catalyst precursor composite supports a catalyst precursor instead of the catalyst 120 in the catalyst composite 100. The catalyst precursor comprises a support 122, a precursor of a catalytically active metal 121, and a compound produced from the precursor. In order to finally produce the catalytically active metal 121, the catalyst precursor preferably contains at least one of Ni, Fe, Co, Cu, and Ru.

[0029] The precursor of the catalytically active metal 121 is, for example, an oxide of the catalytically active metal. The mass of the precursor of the catalytically active metal 121 is determined so as to satisfy the above-mentioned mass of the catalytically active metal 121 by adjusting the mass of the precursor of the catalytically active metal 121 to the volume of the catalytic composite 100 (=π·(Do / 2) 2 The concentration of the fluoride (H) is preferably 15 g / L or more, and more preferably 20 g / L or more.

[0030] <Method of manufacturing catalytic composite> An embodiment of a method for producing a catalyst composite according to the present invention will be described. The method for producing a catalyst composite according to the present invention is a method for producing a catalyst composite in which a catalyst for a methanation reaction for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide with hydrogen is supported on a ceramic honeycomb substrate.

[0031] The method for producing a catalyst composite of the present invention is characterized by comprising: a carrier-supported material preparation step of immersing a ceramic honeycomb substrate in a hydrosol containing a carrier material, followed by drying and heat treatment to support the carrier on the ceramic honeycomb substrate to produce the carrier-supported material; a catalyst precursor composite preparation step of impregnating the carrier substrate with an aqueous solution of a salt of a catalytically active metal, followed by drying and heat treatment to support a precursor of the catalytically active metal to produce a catalyst precursor composite; and a catalyst reduction step of heat-treating the catalyst precursor composite to reduce the precursor of the catalytically active metal to produce the catalytically active metal.

[0032] First Embodiment A flow chart showing an embodiment of the method for producing a catalyst composite of the present invention is shown in Fig. 2. The embodiment of the method for producing a catalyst composite includes a carrier support preparation step, a catalyst precursor composite preparation step, and a catalyst reduction step.

[0033] First, in the carrier-supported material preparation step, the ceramic honeycomb substrate 110 is immersed in a hydrosol, and then dried and heat-treated to obtain a carrier-supported material.

[0034] In this case, the components of the hydrosol are not particularly limited, but taking into consideration the cost and the methanation activity of the carrier 122, it is preferable that the hydrosol contains at least one of alumina, ceria, and zirconia. In addition, after taking out the ceramic honeycomb substrate 110 that has been immersed in the hydrosol, it is preferable to remove the hydrosol that has accumulated in the cells 113 before drying. If the hydrosol is not removed, the carrier 122 may be excessively supported, which may unintentionally hinder the inflow of the raw material gas.

[0035] The temperature of the heat treatment in the carrier-supported material preparation step is preferably 500°C or more and 650°C or less. The lower limit of the heat treatment temperature is preferably 500°C or more because it is desirable to perform the heat treatment at a temperature higher than the heat treatment temperature in the catalyst precursor composite preparation step in order to suppress the grain growth of the carrier 122 in the heat treatment in the next catalyst precursor composite preparation step. In addition, if the heat treatment is performed at a temperature exceeding 650°C, the degree of grain growth increases, and it is assumed that the surface area required for supporting the catalytically active metal 121 cannot be maintained, so the upper limit of the heat treatment temperature is preferably 650°C. The holding time of the heat treatment is preferably 0.5 to 10 hours. This is because heating is insufficient to achieve a uniform temperature if it is less than 0.5 hours, and heating for more than 10 hours not only requires too much time and heat (electricity) for heating, but also there is concern about grain growth of the carrier.

[0036] Next, in the catalyst precursor composite preparation process, the carrier is impregnated with an aqueous solution of a salt of a catalytically active metal containing at least one of Ni, Fe, Co, Cu, and Ru, and then dried and heat-treated to obtain a catalyst precursor composite.

[0037] At this time, the type of catalytically active metal salt is not particularly limited, but for example, nitrates and acetates can be used. The amount of the aqueous solution of the catalytically active metal salt is preferably calculated from the water absorption value measured for the carrier-supported material to determine the volume that can absorb water, and water is added to the weighed catalytically active metal salt so as to be the same volume, to prepare the aqueous solution. In this way, since the amount of the aqueous solution of the catalytically active metal salt is determined from the water absorption amount of the carrier-supported material, it is desirable that the concentration of the catalytically active metal salt in the aqueous solution of the catalytically active metal salt is equal to or lower than the solubility of the catalytically active metal salt at room temperature. When the amount of the catalytically active metal salt to be supported is large, the process can be carried out in several separate steps.

[0038] The heat treatment temperature in the catalyst precursor composite preparation step is preferably 450°C or more and 600°C or less. If the heat treatment temperature is too low, the thermal decomposition of the catalytically active metal salt may be insufficient, so the lower limit is preferably 450°C. The upper limit of the heat treatment temperature is preferably higher than the heat treatment temperature in the catalyst reduction step in order to suppress the grain growth of the support 122 and the catalytically active metal precursor in the heat treatment in the next catalyst reduction step, and is preferably 600°C because it is desirable to perform the heat treatment at a lower temperature than the heat treatment temperature in the previous support support preparation step. The holding time of the heat treatment is preferably 0.5h or more and 5h or less. This is because if it is less than 0.5h, the heating may be insufficient to achieve a uniform temperature, and if it exceeds 5h, too much time and heat (electricity) for heating is required.

[0039] Finally, in the catalyst reduction step, the catalyst precursor composite is heat treated to reduce the catalytically active metal salt to the catalytically active metal.

[0040] The heat treatment atmosphere at this time is not limited as long as it can reduce the catalytically active metal precursor, but it is preferable to use a gas atmosphere containing hydrogen and reduce the catalytically active metal precursor by reaction with hydrogen to form a catalytically active metal. The heat treatment temperature is preferably 200°C to 580°C. If the temperature is less than 200°C, the reduction reaction may not be promoted, and it is preferable to perform the heat treatment at a temperature lower than the heat treatment temperature of the previous catalyst precursor preparation step, so it is preferable to perform the heat treatment at 580°C or less. The holding time of the heat treatment is preferably 0.5 to 5 hours. If it is less than 0.5 hours, the temperature may become uniform or the heating may be insufficient to completely finish the reduction reaction, and if it exceeds 5 hours, too much time and heat (electricity) for heating is required. EXAMPLES

[0041] In the following, examples will be described in which the amount of the carrier and the amount of the catalytically active metal (the amount of the precursor of the catalytically active metal) are changed.

[0042] First, ceramic honeycombs 1 to 8 made of cordierite were prepared for use in producing catalyst composites 1 to 6 as examples and catalyst composites 7 to 8 as comparative examples. These were machined using a hole saw with an inner diameter of φ20 mm to have an outer diameter Do of 20 mm and a height H of 50 mm to obtain ceramic honeycomb substrates 1 to 8. The cell density of each of the ceramic honeycomb substrates 1 to 8 is shown in Table 1.

[0043] The amount of water absorption was measured for these ceramic honeycomb substrates 1 to 8 before they were subjected to the carrier loading process. The measurement method is as follows. First, water was gradually absorbed from one end face of the ceramic honeycomb substrate. After that, the sample was turned over and the end face opposite to the end face that had absorbed water was placed on thin paper, and water absorption and confirmation were repeated until water was attached in a lattice pattern to the thin paper. When water was attached in a lattice pattern to the thin paper, water absorption was deemed complete, and the mass at that point was measured. Finally, the difference with the mass in a dry state was calculated, and this was used as the total volume (=π·(Do / 2) 2The water absorption was calculated by dividing the measured water absorption by 1.0 μm × 1.0 μm. The water absorption was then measured in the same manner.

[0044] Next, the ceramic honeycomb substrates 1 to 7 were loaded with a carrier to obtain carrier-loaded materials 1 to 7. The specific method is described below. Nanoparticles of alumina hydrate were used as the carrier, and the ceramic honeycomb substrates 1 and 5 were immersed in an alumina sol stock solution containing granular nanoparticles of the order of 10 to 100 nm, and the ceramic honeycomb substrates 2 to 4 and 6 were immersed in diluted alumina sol. The excess alumina sol was removed with compressed air, and then the substrates were dried in a microwave dryer and heat-treated at 600 ° C for 1 h using an electric furnace. This carrier loading process was repeated for each of the catalyst composites 1 to 7 until the target carrier loading amount was reached, to obtain carrier-loaded materials 1 to 7. The carrier loading amount is as shown in Table 1. In addition, the water absorption amount of the obtained carrier-loaded materials was measured before the catalyst precursor was loaded.

[0045] Next, catalytically active metal salt was supported on the carrier supports 1 to 7 and the ceramic honeycomb substrate 8 to obtain catalyst precursor composites 1 to 8. The specific method is described below. For each of the catalyst composites 1 to 8, the mass of nickel (II) nitrate hexahydrate was calculated and weighed so as to obtain the target Ni loading amount. Water was added to the weighed nickel (II) nitrate hexahydrate to prepare an aqueous nickel nitrate solution, and the entire amount of the aqueous solution having the nickel nitrate amount corresponding to each of the catalyst composites 1 to 8 was impregnated into the carrier supports 1 to 7 and the ceramic honeycomb substrate 8 and dried. Then, heat treatment was performed at 520°C for 2 hours to obtain catalyst precursor composites 1 to 8 for each of the catalyst composites 1 to 8.

[0046] Finally, the catalytically active metal salts in the catalyst precursor composites 1-8 were reduced to obtain catalyst composites 1-8. The specific method is described below. Each was inserted into a SUS reaction tube with an inner diameter of φ20.5 mm, and the reaction tube was placed in an electric furnace. While introducing a mixed gas with a molar ratio of H2:Ar=1:4 into the reaction tube at a flow rate of 1.5 NL / min, heat treatment was performed at 500°C for 2 hours to obtain catalyst composites 1-8. After that, it was cooled once.

[0047] The methane conversion rate was measured for the catalyst composites 1 to 8 thus prepared. The specific method is as follows. After the catalyst composites 1 to 8 were obtained by the reduction heat treatment, the electric furnace was cooled once, and then the temperature at a position 50 mm above the upper end of the catalyst composites 1 to 8 in the reaction tube (hereinafter referred to as the catalyst inlet temperature) was raised to a predetermined temperature. The catalyst inlet temperature at this time was set to the temperature at which the methane conversion rate was highest for each of the catalyst composites 1 to 8. Then, a raw material gas consisting of a mixture of CO2 gas, H2 gas, and N2 gas such that the molar ratio of the reaction gas was CO2:H2:N2=1:4:5 was introduced into the reaction tube at a space velocity of 10,000 h. -1 The methane conversion rate, which is the ratio of CO2 converted to CH4, was calculated by measuring the gas flow rate at the reaction tube outlet and analyzing the gas composition.

[0048] Table 1 shows the results of various measurements on catalyst composites 1-8 and the intermediates during production, namely the ceramic honeycomb substrate, the carrier support, and the catalyst precursor composite. Catalyst composites 1-6, which are examples, all achieved methane conversions of 65% or more under conditions where the catalyst inlet temperature was 300°C or less, demonstrating good performance as a methanation reaction catalyst. On the other hand, the methane conversions of catalyst composites 7 and 8, which are comparative examples, were low at 60.4% and 26.2%, respectively, and both were achieved under conditions where the catalyst inlet temperature exceeded 300°C.

[0049] [Table 1]

[0050] As shown in Table 1, the water absorption per unit volume of the carrier-supported material (before supporting the catalyst precursor) is in the range of 50 to 170 g / L for catalyst composites 1 to 7, and exceeds 170 g / L for catalyst composite 8. Comparing the water absorption per unit volume of the carrier-supported material (before supporting the catalyst precursor), the catalyst inlet temperature, and the methane conversion rate for catalyst composites 1 to 8, it can be seen that catalyst composite 7, whose carrier-supported material (before supporting the catalyst precursor) has a water absorption rate of more than 170 g / L, has a higher catalyst inlet temperature and a lower methane conversion rate than catalyst composites 1 to 6, whose carrier-supported material (before supporting the catalyst precursor) has a water absorption rate of 170 g / L or less. This is thought to be due to the fact that the amount of catalyst supported is small, resulting in the occurrence of parts on the surface of the partition wall 112 of the ceramic honeycomb substrate 110 where the carrier 122 is not supported, or the carrier 122 being supported in a very small amount, which means that a sufficient amount of catalyst cannot be secured for the methanation reaction. It is considered that the methanation activity of the catalyst composite 8 is inferior to that of the catalyst composite 8 which does not support the carrier 122, because the catalyst composite 8 does not support the carrier 122. Therefore, it was found that when the water absorption amount of the carrier support (before supporting the catalyst precursor) is greater than 170 g / L, the catalyst inlet temperature needs to be increased and the methane conversion rate decreases.

[0051] From the above, it was found that, according to the catalyst composites 1 to 6 corresponding to the present invention, a high methane yield exceeding 65% can be obtained at a catalyst inlet temperature of 300° C. or less. [Explanation of symbols]

[0052] 100: Catalytic complex 110: Ceramic honeycomb substrate 111:Outer wall 112: Bulkhead 113: Cell 114: Pore 120: Catalyst 121:Catalytically active metal 122: Carrier

Claims

1. A catalyst composite in which a catalyst for a methanation reaction for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide is supported on a ceramic honeycomb substrate, The catalyst comprises a catalytically active metal and a carrier supporting the metal, A catalyst composite, characterized in that the carrier supported on the ceramic honeycomb substrate has a water absorption per unit volume of 170 g / L or less.

2. A catalyst precursor composite in which a precursor of a methanation reaction catalyst for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide is supported on a ceramic honeycomb substrate, The catalyst precursor comprises a precursor of a catalytically active metal or a compound produced from the precursor of the catalytically active metal, and a support supporting the precursor or the compound; A catalyst precursor composite, characterized in that the carrier supported on the ceramic honeycomb substrate has a water absorption per unit volume of 170 g / L or less.

3. A method for producing a catalyst composite in which a catalyst for a methanation reaction for methanating hydrogen by reacting a gas containing at least one of carbon dioxide and carbon monoxide is supported on a ceramic honeycomb substrate, a carrier-supported material preparation step of immersing the ceramic honeycomb substrate in a hydrosol containing a carrier material, followed by drying and heat treatment to prepare the carrier-supported material in which the carrier is supported on the ceramic honeycomb substrate; a catalyst precursor composite preparation step of impregnating the carrier with an aqueous solution of a salt of a catalytically active metal, followed by drying and heat treatment to prepare a catalyst precursor composite carrying a precursor of the catalytically active metal; a catalyst reduction step of reducing the precursor of the catalytically active metal to the catalytically active metal by heat treating the catalyst precursor composite; A method for producing a catalytic composite, comprising:

Citation Information

Patent Citations

  • Co2 methanation catalyst and carbon dioxide reduction method using the same

    JP2019155227A